De novo Assembly and Characterization of the Floral Transcriptomes of Two Varieties of Melastoma malabathricum - Zheng, Tao; Lin, Yihua; Wang, Longping; Lin, Qiujin; Lin, Xiuxiang; Chen, Zhendong; Lin, Zhenyue (Frontiers in Genetics, 2019)
Melastoma malabathricum is an important medicinal and landscape plant that is globally distributed in temperate and subtropical regions. However, available genomic information for the entire Melastomataceae family is notably limited. In view of the application potential of floral parts in secondary metabolite extraction, we characterized for the first time the floral transcriptomes of two key M. malabathricum varieties, purple variety and white variety. Our transcriptome assembly generated 52,498 and 49,380 unigenes with an N50 of 1,906 and 1,929 bases for the purple and white varieties, respectively. Comparative analysis of two transcriptomes demonstrated that they are highly similar but also highlighted genes that are presumably lineage-specific, which explains the phenotypes of each variety. Additionally, a shared transcriptional signature across the floral developmental stages was identified in both M. malabathricum varieties; this signature included pathways related to secondary metabolite synthesis, plant hormone signalling and production, energy homeostasis and nutrient assimilation pathways and cellular proliferation. The expression levels of flavonoid accumulation and candidate flavonoid biosynthesis-related genes in M. malabathricum flower development stages validated the transcriptome findings. The transcriptome data presented in this study will serve as a valuable resource for future work on the exploitation of M. malabathricum and other related species. The gene expression dynamics during flower development will facilitate the discovery of lineage-specific genes associated with phenotypic characteristics and will elucidate the mechanism of the ontogeny of individual flower types.